An Analysis of Canadian Doctor of Pharmacy Student Experiences in Non-Traditional Student-Preceptor Models - McIntyre, Caitlin (Am J Pharm Educ, 2019)
Objective. To describe students’ experiences and perceptions of non-traditional student-preceptor learning models and evaluate the effectiveness of these models on students’ learning experience. Methods. Pharmacy students who had completed at least one experiential rotation with a non-traditional learning model participated in semi-structured interviews. Models included peer-assisted learning (PAL; two or more students of same educational level), near-peer teaching (NPT; one or more junior students with one or more senior students), and co-preceptorship (CoP; two or more preceptors). Interviews were transcribed, coded, and analyzed for themes. Themes were mapped according to the Kirkpatrick model for evaluating educational training. Results. Twenty semi-structured interviews were conducted. Forty-three experiences (19 CoP, 14 PAL, 10 NPT) from 14 institutions were described. Many themes overlapped between the three models. In CoP, learners described increased preceptor availability and exposure to different patient care approaches. Challenges arose when preceptors had different expectations. Students overwhelmingly endorsed a multi-learner environment. Both PAL and NPT learners felt supported as collaboration with other learners was readily fostered. Potential challenges in PAL and NPT were difficulties when personalities conflicted and when there was a significant knowledge gap between the learners. All three models allowed for the development of skills, including communication and collaboration. Learners reported an enhanced approach to patient care and professional practice, including approaches to teaching as new preceptors. Conclusion. Pharmacy students and graduates valued their experiences in non-traditional student-preceptor models. Institutions may find support for using these precepting models to increase placement capacity.